2016
DOI: 10.16986/huje.2016015868
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye de Öğrencilerin Akademik Başarısını Etkileyen Faktörler:

Abstract: Öz: Bu çalışmanın amacı, Türkiye'de öğrencilerin akademik başarısını etkileyen faktörlerin incelenmesidir. 2000-2015 yılları arasında Türkiye'de gerçekleştirilen 62 çalışma, meta-analiz yöntemi kullanılarak analiz edilmiştir. Araştırmada etki büyüklüğü indeksi olarak korelasyon katsayısı kullanılmıştır. Korelasyon katsayıları rastgele etkiler modeline göre Fisher z yöntemiyle birleştirilmiştir. Bu bağlamda çalışmada, korelasyon dönüşümleri, etki büyüklüğü, anlamlılık ve heterojenlik testleri için "Comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
46

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 6 publications
3
27
0
46
Order By: Relevance
“…Moreover, the analyses suggested that the students" ESCS was perceived to be the most important effect on their reading, mathematics, and science achievement. This finding is also supported by various studies (Dinçer and Kolaşin, 2009;Ferrera et al, 2011;Finch and Marchant, 2013;Geske et al, 2006;Nonoyama, 2005;Oral and Mcgivney, 2014;Sarıer, 2016;Xu, 2006;Wolfram, 2005). For example, in the study by Yildirim (2009) concerning the PISA 2006 results, the primary elements that determined the quality of education in Turkey were reported to be the educational level and profession of the mother and father as well as the resources students had at home including socio-economic and socio-cultural factors.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 77%
“…Moreover, the analyses suggested that the students" ESCS was perceived to be the most important effect on their reading, mathematics, and science achievement. This finding is also supported by various studies (Dinçer and Kolaşin, 2009;Ferrera et al, 2011;Finch and Marchant, 2013;Geske et al, 2006;Nonoyama, 2005;Oral and Mcgivney, 2014;Sarıer, 2016;Xu, 2006;Wolfram, 2005). For example, in the study by Yildirim (2009) concerning the PISA 2006 results, the primary elements that determined the quality of education in Turkey were reported to be the educational level and profession of the mother and father as well as the resources students had at home including socio-economic and socio-cultural factors.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 77%
“…Bu çalışma kapsamında da sınıf öğretmeni adaylarının öğrenme stillerinin akademik başarılarını yordadığı ve akademik başarının %36'sını açıkladığı belirlenmiştir. Akademik başarı üzerinde motivasyon, öz yeterlilik, tutum, sosyo-ekonomik düzey, anne-baba eğitim düzeyi, ders çalışma alışkanlığı gibi birçok bağımsız değişkenin etkisinin olduğu düşünüldüğünde (Sarıer, 2016) öğrenme stillerinin akademik başarıyı açıklama yüzdesi oldukça önemlidir.…”
Section: Tartişma Ve Sonuçunclassified
“…Proportion of variance explained by learning styles is notably significant when it is considered that academic success is affected by a large number of independent variables such as motivation, self-efficacy, attitude, socio-economic level, parents' educational status, studying habits, etc (Sarıer, 2016). When significance tests are analyzed, it is found out that avoidant and dependent learning styles significantly predict academic success, speaking specifically, as avoidant learning styles decrease and dependent learning styles increase, academic success increases.…”
Section: Tartişma Ve Sonuçmentioning
confidence: 99%
“…Akademik başarıyı etkileyen faktörler genellikle öğrenciden, okuldan ve aileden kaynaklanan faktörler olarak gruplandırılmaktadır. Örneğin Türkiye'de öğrencilerin akademik başarısını etkileyen faktörlerin incelendiği bir araştırmada (Sarıer, 2014), 2000-2015 yılları arasında yapılan 62 çalışma, meta-analiz yöntemi kullanılarak analiz edilmiştir. Bu araştırmada öğrenci okul ve aile kaynaklı faktörler incelenmiş, okulla ilgili faktörlerin öğrencilern başarısına etki büyüklüğü 0.231, öğrenciyle ilgili faktörlerin öğrencilerin başarısına etki büyüklüğü.324 ve aileyle ilgili faktörlerin etki büyüklüğü .271 olarak bulunmuştur.…”
Section: Introductionunclassified
“…Bu araştırmada öğrenci okul ve aile kaynaklı faktörler incelenmiş, okulla ilgili faktörlerin öğrencilern başarısına etki büyüklüğü 0.231, öğrenciyle ilgili faktörlerin öğrencilerin başarısına etki büyüklüğü.324 ve aileyle ilgili faktörlerin etki büyüklüğü .271 olarak bulunmuştur. (Sarıer, 2014). 20.…”
Section: Introductionunclassified